APPLICATION OF UMRA AND RUQBA IN DISBURSEMENT OF FAMILY TAKAFUL BENEFIT: AN ANALYSIS FROM SHARIAH PERSPECTIVE - Md. Habibur Rahman; Md. Faruk Abdullah; Puspa Liza Ghazali; Noor Mohammad Osmani (Asian Academy of Management Journal, 2019)
The paper aims to analyse the validity of practicing umra and ruqba concepts in disbursement of family takaful benefit from the shariah perspective. In the current practice of takaful, the disbursement of family takaful benefit is subject to the demise of takaful certificate holder. Upon maturity of the certificate, if the certificate holder is alive, he will enjoy takaful benefit but not the beneficiary or hibah recipient. Accordingly, he takes back the donation that he made earlier, which makes the arrangement contentious, as long as the Islamic value is concerned. To resolve this issue, the paper suggested that the takaful benefit could be disbursed based on umra and ruqba concepts as they are subject to the survival of the contracting parties. Umra and ruqba are valid provided that once the donation is executed, the donated object should never be returned to the donor. These concepts are appropriate for takaful because the beneficiary can enjoy takaful benefit only when the certificate holder dies before the maturity of certificate. Once the certificate holder dies, takaful benefit cannot be provided to him. The paper argues that the application of umra and ruqba concepts minimises the consequential issues that arise when takaful benefit is disbursed by nomination or inheritance or absolute hibah. Analysing the opinions of the classical Islamic jurists, the paper concludes that the application of umra and ruqba in disbursement of takaful benefit could be done with a structured checklist form.